A importância do Conselho Superior do Ministério Público na tutela dos direitos transindividuais: a atuação do colegiado no Estado de São Paulo na área dos direitos das pessoas com deficiência - Serrano, Yolanda Alves Pinto (2023)
The Public Prosecutor's Office, after enactment of the 1988 Constitution, became one of the constitutional institutions for development; holding universal competence - and the most active and proactive - in the defense of the metaindividual rights. In order to fulfill its mandate, the agency has special and exclusive instruments that enable it to act to resolve collective conflicts, among which is the civil inquiry. It is in the context of this procedure that the Prosecutors’ Office’s action has proved to be more innovative, with the adoption of measures that avoid judicialization and achieve very efficient practical results. The Superior Council of the Public Prosecutor's Office is the body that reviews the ministerial extrajudicial action, and the objective of this dissertation was to dissect such executive activity of the collegiate in the field of meta-individual rights. To this end, detailed theoretical research was carried out on the procedures and instruments on which the collegiate reviewing decision can fall; we also sought to outline the profile and attributions of the CSMP. For methodological purposes, it was decided to restrict the research to the Superior Council of the Public Prosecutor's Office of the State of São Paulo and to the rights of people with disabilities. Quantitative and qualitative data related to the collegiate reviewing activity was gathered and some cases in which intervention changed the outcome of the investigation were duly analyzed. In the end, it was concluded that the collegiate review function has great transformative potential, both in the sense of correcting mistakes and of standardizing the actions of the primary enforcement agencies